Ein Prognosemodell für die Verwitterung von Sandstein - Kotan, Engin (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2017)
Sandstone is the most common kind of natural stone used for historic buildings in Central Europe. During the past century a dramatic increase in different types of damage to historic buildings, monuments and sculptures made from natural stone has been observed. The present work deals with theoretical aspects of strength loss, fracture processes and degradation during the decay processes.